Septoplasty can be adopted as a Daycare Surgery - Farooq, Muhammad (International Journal of Pathology, 2018)
Presently Septoplasty is being performed as admitted case by most of Otorhinolaryngologists and anterior nasal packaging is applied for about 24 hours, which is not free of complications.Objective: To study the significance of early (after about 4 hours) removal of nasal packing after Septoplasty and its feasibility as daycare surgery.Patients and Methods: This was a prospective and experimental study conducted on 100 patients for 18 months, who were operated for symptomatic deflected nasal septum (DNS). Patients were randomly divided into two equal groups. In Group-A admitted patients, after septoplasty nasal packing was removed after 24 hours and in Group-B after septoplasty, it was removed after about 4 hours; allowing patients to go home after 5-6 hours. Patient’s discomfort caused by nasal packing was evaluated by means of a visual analog scale from zero to 10. Post-operative complications of septoplasty were also compared in both groups.Results: Patients discomfort score due to nasal packing and complications of septoplasty were found significantly less in Group-B as compared to Group-A.Conclusion: Early removal (after about 4 hours) of nasal packing following septoplasty was more comfortable and beneficial as compared to removal of nasal packing after 24 hours. It also made septoplasty a day care, more cost effective and convenient operation.